Resumption, A’- chains and implications on clausal architecture - Meral, Hasan Mesud. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This work investigates the nature of resumption and provides an analysis of how anaphoric dependencies occur in language. I raise the question whether resumption has any explanatory power on various grammatical phenomena such as binding, control and null object licensing which have been assumed in the generative literature as resulting from different licensing mechanisms and require different grammatical operations. In this respect, this study aims at extending the applicational domain of resumption from relative clauses to anaphor licensing, control and null object licensing. I claim that resumption offers a valid solution which compromises the different requirements of these different phenomena with respect to locality. The idea in the dissertation is that the anaphors, PROs and null objects behave in the same way with a resumptive in that they form a unit with their syntactic antecedents (empty operator), then they split. The antecedent binds the grammatical formative inside the clause respecting a different sense of locality. The dissertation also argues that the A- domain in Turkish is weak due to the problematic nature of A- domain operations. Instead, what Turkish instantiates is a rich A’- domain where different grammatical phenomena such as binding and control are licensed via operator-variable chains akin to resumption. For the problematic aspects of Binding Theory conditions and the lack of pronoun-anaphor complementarity, the dissertation argues that Turkish follows a threepartite system where a third category exemplified by a complex pronominal expression (kendi)si subsumes the functions of regular pronominals and anaphors and other functions which cannot be expressed by these two grammatical formatives.
Keywords: Minimalist theory (Linguistics); Turkish language -- Grammar.